The CDS basis in the European market - Thomas Heidorn; Juergen Klaus; Riccardo Mazzalupi (Frankfurt School of Finance & Management, 2026)
The relationship between Credit Default Swaps (CDS) and cash bonds plays a pivotal role in providing market participants with important information which directly affects investment and risk management strategies. Particularly relevant is the CDS-Bond basis, defined as the difference in basis points (bps) between CDS and the reference entity bond spread. Understanding the drivers behind CDS-Bond basis behavior enables more informed decisionmaking that reflects underlying credit market dynamics. This working paper analyzes the CDSBond basis in the European market, focusing on the constituents of the Markit iTraxx Europe index between March 2020 until March 2025. The analysis addresses basis behavior at the aggregate index level and across sectors. At an index level a mean reverting pattern has been identified with a negative basis average over the sample observed. In the sectorial analysis a strong heterogeneity emerges, with Autos featuring a more positive basis compared to Financials in a deeply negative basis territory affected by Credit Suisse shock. Finally, practitioner insights are integrated to contextualize these findings, emphasizing liquidity asymmetries, execution constraints, and differences in information absorption between CDS and cash bond markets offering actionable insights for credit market partecipants, and laying a solid foundation for further research.
Keywords: 330; CDS-Bond basis; Sectorial CDS basis; credit spread; iTraxx Europe basis